Cover Image, Volume 22, Issue 11. Issue 11 (19th October 2020) - Meneghini, Luigi F.; Sullivan, Sean D.; Oster, Gerry; Busch, Robert; Cali, Anna M. G.; Dauchy, Arnaud; Gill, Jasvinder; Bailey, Timothy S.
Abstract : The outside back cover image is based on the Original Article A pragmatic randomized clinical trial of insulin glargine 300 U/mL versus first‐generation basal insulin analogues in insulin‐naïve adults with type 2 diabetes: 6‐month outcomes of ACHIEVE Control by Luigi F. Meneghini et al., https://doi.org/10.1111/dom.14152 .